Images of this Present Life in the Rhetoric of John Chrysostom - Laird, Raymond (Scrinium, 2015)
In determining the attitude of John Chrysostom to life in this present age, examination is made of the various images that this great rhetorician of the Church used in his homilies and writings. It could be said that the power of his oratory reaches its apex in the images frequently employed throughout the corpus of his extant works. This is no less the case in his references to our earthly lives. Inevitably linked with his pastoral concerns about human passions that endanger spiritual growth, the canvas for the main part is filled with images of disdain for and warning of worldly values, and of encouragement to focus on the heavenly riches.